2013
DOI: 10.1002/ajmg.a.35738
|View full text |Cite
|
Sign up to set email alerts
|

Simpson–Golabi–Behmel Syndrome Type 1 and Hepatoblastoma in a Patient With a Novel Exon 2–4 Duplication of the GPC3 Gene

Abstract: Mutations in the gene encoding glypican (GPC) 3 appear to be responsible for most cases of Simpson-Golabi-Behmel syndrome type 1. Duplication of the GPC4 gene has also been associated to this syndrome; however, no duplications involving GPC3 have been related. We describe a family that harbors a novel exon 2-4 duplication event leading to a truncating germline mutation of the GPC3 gene that, to our knowledge, has not been previously reported. GPC3 transcripts that carry this duplication bear non-functional pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In the May issue of the Journal, Mateos et al [2013] reported a case of Simpson-Golabi-Behmel syndrome (SGBS), with a novel mutation of the GPC3 gene consisting of a duplication of exons 2-4 which causes a frameshift leading to a protein truncated of its last 183 amino-acids including the C-terminus. This report pinpointed that duplication of the GPC3 gene had not been reported before.…”
Section: To the Editormentioning
confidence: 98%
“…In the May issue of the Journal, Mateos et al [2013] reported a case of Simpson-Golabi-Behmel syndrome (SGBS), with a novel mutation of the GPC3 gene consisting of a duplication of exons 2-4 which causes a frameshift leading to a protein truncated of its last 183 amino-acids including the C-terminus. This report pinpointed that duplication of the GPC3 gene had not been reported before.…”
Section: To the Editormentioning
confidence: 98%
“…Endocrine abnormalities seen with SGBS include neonatal hypoglycemia due to pancreatic hyperplasia of the islets of Langerhans and newborn bone age advancement [Neri et al, ; Chen et al, ; Baujat et al, ]. As with other overgrowth syndromes, patients with SGBS are at increased risk for certain tumors, including Wilms tumor, hepatoblastoma, hepatocellular carcinoma, gonadoblastoma, and neuroblastoma [Behmel et al, ; Golabi and Rosen, ; Neri et al, ; Mateos et al, ]. Recently a case of SGBS with medulloblastoma has been reported [Thomas et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, the Wnt-promoting factor R-spondin 3 was shown to interact with Syndecans and Glypican3 (Ohkawara et al, 2011), suggesting a complex interaction of heparan sulphate proteoglycans and Wnt signaling components at the cell membrane. Interestingly, human SGBS patients have a tendency to develop pre-and postnatal tumors, such as Wilm's tumor, hepatoblastomas, neuroblastomas and gonadoblastomas (Golabi et al, 1993;Rodríguez-Criado et al, 2005;Thomas et al, 2012;Mateos et al, 2013). The development of these tumors has been brought into correlation with a misregulation of canonical Wnt signaling (Honecker et al, 2004;Lapunzina, 2005;Liu et al, 2008;Armengol et al, 2011), indicating that the lack of glypicans might result in a misregulation of canonical Wnt signaling in SGBS patients.…”
Section: Discussionmentioning
confidence: 99%